MEDIA PEMBELAJARAN INTERAKTIF BERBASIS GAMIFIKASI MELALUI MODEL PROJECT BASED LEARNING (PJBL) UNTUK MENINGKATKAN KEMAMPUAN NUMERASI PESERTA DIDIK KELAS VII MTs AZ-ZAINUDDIN - Muhaemin; Nanang Diana; Nur Fitrianingsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Numeracy skills are one of the essential competencies that students must possess to face the challenges of 21st-century learning. However, students' numeracy skills remain relatively low due to conventional teaching practices, limited student engagement in the learning process, and the lack of interactive learning media. These conditions result in low learning motivation, limited participation, and difficulties in solving numeracy problems related to real-life situations. This study aims to develop gamification-based interactive learning media integrated with the Project Based Learning (PjBL) model to improve the numeracy skills of seventh-grade students at MTs Az-Zainuddin. The study employed the Research and Development (R&D) method using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 20 seventh-grade students of MTs Az-Zainuddin. The research instruments included expert validation questionnaires, student response questionnaires, observation sheets, and numeracy tests in the form of pretests and posttests. Data were analyzed using descriptive statistics to determine the validity and practicality of the developed media, while the N-Gain test was used to measure its effectiveness in improving students’ numeracy skills. The product developed is a gamification-based digital learning medium that incorporates numeracy materials, points, levels, challenges, feedback, and project activities aligned with the syntax of Project Based Learning. The results are expected to demonstrate that the developed media is valid, practical, and effective, making it a promising alternative for innovative numeracy learning in the digital era.